Intention to Continue with Ivermectin Treatment for Onchocerciasis Control after Eight Years of Annual Distribution in Cameroon, Nigeria, and Uganda. (April 2013) - Okeibunor, Joseph C.; Brieger, William R.; Abiose, Adenike O.; Elhassan, Elizabeth; Ndyomugyenyi, Richard; Wanji, Samuel; Amazigo, Uche V.
This study identified the socio-demographic correlates of intention to comply with ivermectin treatment, from a structured interview of 2, 306 persons aged 10 years and above, grouped into high and low compliers, who took ivermectin 6–8 times and 0–2 times respectively. Simple descriptive statistics were employed in characterizing the respondents into high and low compliers, while some socio-demographic and key perceptual factors were employed in regression models constructed to explain levels of compliance among the respondents. Demographic and perceptual factors associated with intention to comply with prolonged treatment with ivermectin were identified. Intention to comply was higher among married persons (91.8%, p < 0.001); local populations (89.8%, p < 0.001); and those with history of complying with treatment (98.2%, p < 0.001). Perception of onchocerciasis and effectiveness of ivermectin influenced intention to continue. The perceptual factors that drive the intention to comply should inform plans for health education at the project and village levels.